Dilemmas in Rescue and Reintegration: A critical assessment of India’s policies for children trafficked for labour exploitation - Donger, Elizabeth; Bhabha, Jacqueline (Anti-Trafficking Review, 2018)
This paper provides a comprehensive analysis of the Indian government’s efforts to combat pervasive child trafficking for labour exploitation through rescue and reintegration of affected children. It evaluates the extensive policy and legal frameworks against on-the-ground realities in the states of Bihar and Rajasthan, using empirical findings from a qualitative study carried out by the FXB Center for Health & Human Rights at Harvard University. The results demonstrate that current practices fail to adhere to human rights norms or protect rescued children from risk of future exploitation. They underscore important challenges in the rescue and reintegration of trafficked children, and call into question the singular focus on this category of post-harm response over preventative interventions. The findings point to a critical need for future research, sustained multi-stakeholder discussion and concrete reforms.